Fleming's Defense Mechanisms In Stephen Crane's The Red Badge Of Courage - Anshori, Adam (English Education Department, Universitas Islam Indonesia, 2011)
This paper is an attempt to discuss the personality of Henry Fleming, a fiction character in the novel the “Red Badge of Courage. The problem statement in this paper is “What defense mechanisms which occur in Fleming's character”? This study used American Studies theory by Robert Meredith which agrees that the American Studies approach needs more than one academic discipline. The reconciliation of academic discipline enables the writer uses psychological approach. According to Wilbur S. Scott the application of psychological knowledge can generate three kinds of study and analysis: a more precise language with which to discuss the creative process, a study of lives of authors, and the use of psychology to analyze fictional characters. The theories of psychology were taken from Sigmund Freud's Psychoanalysis: A General Introduction to Psychoanalysis (2002), Sigmund Freud's The Ego and The Id (1962), and Anna Freud's The Ego and Defense Mechanism (1948). The result of the study shows that there are a total of 25 acts of defense mechanisms conducted by Fleming in this novel. Henry acts all of the ten defense mechanisms from Anna Freud's theory. The primary act of denial is refusing to accept the condition Henry is facing and even lying to his own comrades. The acts of regression are not to talk to his own comrades either to help or just ignoring his comrades. Most of the acts of fantasy are about the ideal war in Henry's perspective which in reality was far from it. In the acts of displacement, most are by blaming his comrades and his generals instead of the enemy. The act of sublimation is conducted by hiding his fear and projecting his confidence. In the act of projection, Henry is projecting his insecurities to his enemy and his generals. Henry's act of rationalization is by justifying his flee from the battle. Henry's act of intellectualization is by 2 letting his thought overcome his act. The act of repression is by forgetting the fact that he is dependant to someone. And in the last, the act of reaction formation is by attacking the enemy in order to hide his fears.